A comparative study of psychosocial morbidity in stable versus unstable vitiligo - Swapna S Khatu; Sharmishtha S Deshpande; Neeta R Gokhale; Deepak Khismtarao; Dipali C Chavan (Wolters Kluwer Medknow Publications, 2018)
Context: Vitiligo is a cosmetically disfiguring condition especially in dark-skinned individuals, thereby adversely affecting their quality of life (QOL). Studies have reported higher psychiatric morbidity in patients with vitiligo, but a comparative study between patients with stable and unstable vitiligo has not been reported. Aims: To compare the psychiatric morbidity, perceived stress, and QOL in patients suffering from stable versus unstable vitiligo. Settings and Design: This was a clinical observational, cross-sectional liaison study conducted over a period of 2 years and included 100 consecutive patients with vitiligo, who came for treatment to the dermatology clinic of a tertiary care hospital. Materials and Methods: A dermatologist clinically assessed the patients and calculated their vitiligo area severity index score and dermatology life quality index. A psychiatrist evaluated the patients on the basis of the perceived stress scale (PSS), hospital anxiety and depression scale (HADS), and clinically established diagnosis using International Classification of Diseases (ICD-10). Statistical Analysis: The aforementioned variables between the two groups were compared using chi-square test and independent t test. Results: High psychiatric morbidity (65%) was reported in patients with vitiligo, with adjustment disorder being the most common morbidity. The most common reported stress was grief or emotionally significant loss. Psychiatric morbidity, scores on HADS, and PSS were significantly higher in patients with unstable vitiligo in comparison to patients with stable vitiligo. The quality of life (QOL) was mildly affected among the patients in both the groups. Conclusions: There is higher psychiatric morbidity in patients with unstable vitiligo along with a worse QOL in comparison to those with stable vitiligo. Patients with vitiligo should be assessed for stability as well as psychiatric morbidity, because it will have significant management implications.